FACTORS AFFECTING ONLINE LEARNING MEDIA DURING THE COVID-19 PANDEMIC AT SCHOOL BATAM CITY STATE BASIS - Hidayat Hidayat; Jon Kenedi; Mursal Mursal (SEAN Institute, 2022)
This study was conducted to determine the effect of teaching method variables, use of learning media, teaching materials, time utilization, student behavior, and learning facilities on online learning media variables during the Covid-19 pandemic, the study population was 5,975 teachers spread across 144 schools. Based on the State of Batam City, the sampling method according to Hair et al., (2014) in this study there are 45 question items, so the sample required is a minimum of 45 x 5 = 225 respondents. took 30 days to distribute the questionnaires that were distributed via the Google Form link, after the data was collected and then processed and analyzed further researchers. Based on data analysis, it shows the results of hypothesis testing as has been shown in the t test results that the variables of teaching methods, teaching materials, student behavior and learning facilities have a significant effect, while the variables of learning media use and time utilization has no significant effect on online learning media in this case. The results of the F test have a significant effect simultaneously on the independent variable on the dependent variable.